TRADIÇÃO E CIÊNCIA: UMA PROPOSTA DE SEQUÊNCIA DE ENSINO INVESTIGATIVA E INTERDISCIPLINAR SOBRE O USO DE PLANTAS MEDICINAIS - Tosta, Efigenia Monteiro (2020)
This study proposes a sequence of investigative and interdisciplinary teaching (SEII), which aims to overcome the fragmentation of curricular subjects and launches a coordinated action with the Biology, Chemistry, History and Portuguese teachers, recogniz